2017
DOI: 10.1108/ijoem-10-2014-0169
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of foreign direct investment in developing countries: a panel data study

Abstract: Purpose The purpose of this paper is to identify key determinants of foreign direct investment (FDI) inflows in developing countries by using unbalanced panel data set pertaining to the years 1990-2012. This study considers 20 developing countries from the whole of South, East and South-East Asia. Design/methodology/approach Using seven explanatory variables (market size, trade openness, infrastructure, inflation, interest rate, research and development and human capital), the authors have tried to find the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
112
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(125 citation statements)
references
References 70 publications
11
112
0
2
Order By: Relevance
“…Grohand and Wich (2012) examined the FDI inflows to emerging countries and used the composite index to summarise a number of socio-economic variables and found that the FDI inflows were concentrated in developed countries while in the emerging economies FDI is less attracted due to the poor political, legal system and meagre infrastructure. Some studies have digged-in deeper by undertaking the influence of macro-economic variables on FDI inflows (Bevan & Saul, 2000;Banik, 2003;Cevis & Camurdan, 2007;Khachoo & Khan, 2012;Kumari & Sharma, 2017) and suggested market size, total reserves, infrastructure, trade openness, interest rate human capital yield, and labour costs are the main variables responsible for attracting inflows of FDI in emerging economies. Chakraborty and Basu (2002) found unidirectional causality between FDI and economic growth and bi-directional causality from economic growth to FDI only for India.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Grohand and Wich (2012) examined the FDI inflows to emerging countries and used the composite index to summarise a number of socio-economic variables and found that the FDI inflows were concentrated in developed countries while in the emerging economies FDI is less attracted due to the poor political, legal system and meagre infrastructure. Some studies have digged-in deeper by undertaking the influence of macro-economic variables on FDI inflows (Bevan & Saul, 2000;Banik, 2003;Cevis & Camurdan, 2007;Khachoo & Khan, 2012;Kumari & Sharma, 2017) and suggested market size, total reserves, infrastructure, trade openness, interest rate human capital yield, and labour costs are the main variables responsible for attracting inflows of FDI in emerging economies. Chakraborty and Basu (2002) found unidirectional causality between FDI and economic growth and bi-directional causality from economic growth to FDI only for India.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Theory of economics purports that human capital in the shape of education is one of the potent determinants for the influx of FDI (Dunning, 1977). Most of the studies considered various types of measures as proxies for human capital, of which school enrolment ratios and literacy rate are consistently used (Asiedu, 2002;Azemar & Desbordes, 2009;World Bank, 2018a;Kinda, 2013;Kumari & Sharma, 2017;Okafor et al, 2017). The significance of efficiency entails the following hypotheses:…”
Section: Efficiency-seeking Fdimentioning
confidence: 99%
“…The data is analyzed through statistical models (using STATA 15 software) as fixedeffects model and random-effect model (Kumari & Sharma, 2017). The regression can be formulated as: FDI = α + β1 GDP + β2 GDPP + β3 INFLATION + β4 UNEMPLOYMENT + β5 CCORRUPTION + β6 PSTABILITY + β7 RLAW + β8 VACCOUNTABILITY + β9 GFC + β10 ASPRING + ɛ…………………..(1) Where, FDI is the natural logarithm of FDI; GDP represents the natural logarithm of GDP; GDDP denotes the natural logarithm of GDP per capita; INFLATION is the percentage of interest rates; UNEMPLOYMENT describes the percentage of unemployment; CCORRUPTION is control of corruption percentage; PSTABILITY is the rate of political stability; RLAW explains rule of law percentage; VACCOUNTABILITY denotes the rate of voice and accountability; GFC is the dummy of global financial crisis period; ASPRING is the dummy of Arab Spring period.…”
Section: Regression Of Fdimentioning
confidence: 99%
“…The statistical methods to examine the relationship between FDI and its determinants are fixed-effects model (FEM) and random effects-model (REM) following Bengoa and Sanchez-Robles (2003) and Kumari and Sharma (2017). The paper is organized as follows: part 2 presents the literature review.…”
Section: Introductionmentioning
confidence: 99%